2015
DOI: 10.3945/ajcn.115.111757
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Approaches to Stop Hypertension diet retains effectiveness to reduce blood pressure when lean pork is substituted for chicken and fish as the predominant source of protein

Abstract: The results indicate that adults with elevated BP may effectively incorporate lean pork into a DASH-style diet for BP reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 33 publications
5
46
1
3
Order By: Relevance
“…The Beef in an Optimal Lean Diet Study found that the inclusion of lean beef in a low-saturated-fat DASH-like diet resulted in comparable effects on lipid and lipoprotein measures compared with a standard DASH diet (29). Sayer et al (30) recently showed that a DASH-style diet containing either lean pork or chicken and fish similarly reduced BP. Together with results from the present study, the above findings provide evidence that aspects of the DASH diet can be modified without compromising its benefits on BP or LDL-cholesterol lowering, offering flexibility in food choices for individuals following the DASH diet.…”
Section: Discussionmentioning
confidence: 99%
“…The Beef in an Optimal Lean Diet Study found that the inclusion of lean beef in a low-saturated-fat DASH-like diet resulted in comparable effects on lipid and lipoprotein measures compared with a standard DASH diet (29). Sayer et al (30) recently showed that a DASH-style diet containing either lean pork or chicken and fish similarly reduced BP. Together with results from the present study, the above findings provide evidence that aspects of the DASH diet can be modified without compromising its benefits on BP or LDL-cholesterol lowering, offering flexibility in food choices for individuals following the DASH diet.…”
Section: Discussionmentioning
confidence: 99%
“…CARB, carbohydrate control diet; CHICK, chicken control diet; CON, habitual control diet; F, lean fish control diet; F1, first female group; F1 BEEF, first female group consuming beef diet; F1 PORK, first female group consuming pork diet; F2, second female group; F2 BEEF, second female group consuming beef diet; F2 PORK, second female group consuming pork diet; HC G1, first group consuming high-cholesterol diet; HC G2, second group consuming high-cholesterol diet; LC G1, first group consuming low-cholesterol diet; LC G2, second group consuming low-cholesterol diet; LVLP, lactovegetarian low-protein control diet; M1, first male group; M1 BEEF, first male group consuming beef diet; M1 PORK, first male group consuming pork diet; M2, second male group; M2 BEEF, second male group consuming beef diet; M2 PORK, second male group consuming pork diet; P, poultry control diet; SF, southern fish control diet; TF, tropical fish control diet; VEG, vegetarian control diet. studies containing design features that had the potential to confound results, including weight-loss diets (27,29), hearthealthy diets (25,26,28,34,35,39,42,43), diseased populations [hypertensive (26,28,38), hypercholesterolemic (34,35,42), and/or diabetic (32)], studies that resulted in significant weight loss (25,(27)(28)(29)35), inclusion of processed meat (45), studies that did not specify the degree of meat processing (24,25,27,32,36,40,43,46,47), and studies that used different amounts of protein intake in the control and intervention group or phase (29,32,38,…”
Section: Calculations Bias Assessment and Statistical Analysesmentioning
confidence: 99%
“…The median total red meat servings per day in the control and intervention groups were 0 servings/d (range: 0-0.4 servings/d or 0-30 g/d) and 2 servings/d (or 140 g/d; range 1.0-7.1 servings/d or 68-500 g), respectively. Two of the selected studies included a weight-loss diet (27,29), 8 studies included a heart-healthy dietary pattern (25,26,28,34,35,39,42,43), the subjects self-selected their diet similar to their habitual intake in 9 studies (24, 30, 31, 36-38, 46, 40, 41), and 5 FIGURE 3 Random-effects model meta-analysis for changes in blood LDL-cholesterol concentrations from randomized controlled trials comparing $0.5 or ,0.5 servings of total red meat/d. Heterogeneity: t 2 = 0.011, x 2 = 6.62, df = 38 (P = 0.001), I 2 = 85%.…”
Section: Study Features and Subject Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Faithful cell replication is to be ensured and controlled by restriction points (6). The overexpression of cyclin D1 and E can promote the G/S limiting point of cells and cause excessive cell proliferation; moreover, cell cycle confusion is a key link of the genome (7). It may further increase the probability of carcinogenesis of labile cells, and thereby participate in tumorigenesis and development.…”
Section: Introductionmentioning
confidence: 99%